2022
DOI: 10.26434/chemrxiv-2022-7cl0h
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wastewater-Based Epidemiology for monitoring community derived antimicrobials and resistance genes: a one-year longitudinal study

Abstract: Increasing understanding and awareness of antimicrobial resistance (AMR) is critical in tackling this growing global crisis. Wastewater-based epidemiology (WBE) is a promising approach to monitoring a range of AMR targets in communities through analysis of wastewater. This longitudinal study provides insight into antimicrobial (AA) usage within two communities in the South West of the UK, one city (Bath) and one town (Keynsham). AAs, including metabolites, from a range of different classes were quantified over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(92 reference statements)
1
1
0
Order By: Relevance
“…Two wastewater treatment plants (WWTPs), corresponding to two catchment areas, were selected for this project. This study has previously been reported in Sims et al (Sims et al, 2022). Both sites are within the Southwest of the UK and are a close distance from each other (figure 1).…”
Section: Sampling Sites and Sample Collectionsupporting
confidence: 73%
See 1 more Smart Citation
“…Two wastewater treatment plants (WWTPs), corresponding to two catchment areas, were selected for this project. This study has previously been reported in Sims et al (Sims et al, 2022). Both sites are within the Southwest of the UK and are a close distance from each other (figure 1).…”
Section: Sampling Sites and Sample Collectionsupporting
confidence: 73%
“…AA average loads were, as expected, higher in Bath than in Keynsham (on average 83 ± 24% higher) as AA loads are population size driven. Full breakdowns of loads of all studied AAs can be found in Sims et al (Sims et al, 2022). Seasonal variability of a handful of AAs across different classes was also observed, including MTZ, SLZ, LEX, CIP, and CLR reporting higher loads in winter versus summer.…”
Section: Abundance Of Aas In a 13-months Intercity Longitudinal Studymentioning
confidence: 73%